Value for Money-at-Risk Analysis Model for Green Batching Plant Benefit based National Ready Mix Co Association (NRMCA) Method - Husin, Albert Eddy; Rohman, Muhammad Nur (ASTONJADRO, 2025)
The current green concept trend in Indonesia is contributing to the advancement of sustainability across all industries, including the construction materials sector. The concrete business is crucial because it provides the fundamental components for concrete, which is a critical role it performs in the building process. Throughout the production process, ready-mix concrete has a very negative effect on the environment. Planning and constructing a green concept will be 10-20% more expensive than conventional development. Researchers will use the value for money (VfM)-at-risk analysis model technique to cost-effectively apply the concept of the green concrete industry to statistical analysis and case studies. To improve cost performance, this research updates the knowledge on the green concept for concrete industrial objects and searches for factors that affect its application using partial least square (SEM-PLS) analysis and green concept modeling based on the value for monet at risk analysis model. "10 factors that influence the performance of green costs in the concrete industry" were identified by the research, and they include the following: the risk analysis model, the planning stage, internal costs, production, value for money, the bidding stage, the implementation stage, product use, the operation stage, and maintenance. The application of the VfM-at-risk analysis model was able to increase the green cost performance by 8.66% with a return of 9 years and 2 months by gaining benefits as an environmentally friendly and sustainable concrete industry.